Effect Of Natural Light Glare On Passive Design In Malaysian Government Office Building - Fadli Arabi; Elina Mohd Husini; Mohd Zin Kandar (American Transactions on Engineering & Applied Sciences, 2024)
American Transactions on Engineering & Applied Sciences Vol.1(4) (October 2012)